HIJRA COMMUNITY AND RELIGIOUS MODERATION AMONG MILLENNIALS IN SOLORAYA - Mibtadin, Mibtadin (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2023)
The development of the hijra community in Soloraya has significantly influenced all societal levels, particularly the millennial generation. This research aims to identify the model of religious moderation within the millennial generation in Soloraya, focusing on the hijra community, especially the Legawa and Bi-Adzab communities. Employing a descriptive qualitative approach, the analysis utilizes an interactive model encompassing data reduction, delivery, and conclusion drawing. The Legawa and Bi-Adzab hijra communities leverage public spaces for discourse, promoting a moderate, friendly, and welcoming interpretation of religion. Legawa and Bi-Adzab encourage Islam to enter deep into the public sphere so that it can access facilities properly so as not to threaten democracy and pluralism. These communities advocate for a deeper integration of Islam into the public sphere, ensuring proper access to facilities without compromising democracy and pluralism. Legawa and Bi-Adzab have become symbols of cultural resistance against Islamic movements advocating takfiri ideology and the Islamic caliphate, which are less accommodating of local traditions deemed laisa minal Islam. These communities prioritize local religious traditions in their activities, aiming to shape identity and enhance moral values. They serve as spiritual spaces that strengthen faith and promote a universal respect for local customs. The ultimate goal of Legawa and Bi-Adzab is to elevate the spirituality and religious devotion of the millennial generation.